What we remember : the construction of memory in military discourse - Achugar, Mariana (Discourse approaches to politics, society, and culture, 2008)
This interdisciplinary monograph explores the discursive manifestations of the conflict over how to remember and interpret the actions of the military during the last dictatorship in Uruguay (1973-1985). Through the exploration of the discursive ways in which this powerful group represents past events and participants, we can trace the ideological struggle over how to reconstruct a traumatic past. By looking at memory as a social and discursive practice, the analysis identifies particular semiotic practices and linguistic patterns deployed in the construction of memory. The discursive descript.